Wound monitoring app development - Tan, Jolene Hui Qi (2019)
Due to fast-paced technological advancements, the reliance on a smartphone has grown tremendously over the past few years. People tend to rely on their phones to look for information, to connect with people or to keep track of their daily activities. The existence of a smartphone has brought about much convenience to many lives. And in the global smartphone market, Android phones usage holds the highest percentage. The objective of this project is to develop a wound monitoring Android application for patients or users with chronic wounds that require consistent medical attention after being discharged. The convenience of a smartphone application would encourage users to record down their wound healing process consistently by taking pictures of their wound so as to reduce the risk of wound infection. Doctors can make use of the application to monitor the patient’s wounds in a timely manner and interfere if there are signs of infection. The application would consist of two main functions: to record data and to pick out dominant colours of the image. Before development, the wireframe of the app would be constructed, and the overview of use-case possibilities would be presented. Development of the app is done in Android using React Native, Express.js as a server, and MySQL as a database.